The Inhibitor Pathogen Bacteria’s of Sea Grape Caulerpa lentillifera Applies on Fresh Fish - Alfonsina M. Tapotubun; Imelda K.E. Savitri; Theodora E.A.A. Matrutty (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
AbstractContamination of pathogen bacteries at the fresh fish may occur during the post harvesting to the consuming period, and endanger human health. One of simple and safe way to protect secureness of fresh fish food is the use of Caulerpa lentillifera to push down pathogen bacteries activity. The aims of this research to investigate lability of sea grape (Caulerpa lentillifera) against the activity of pathogen bacteries Escherichia coli, Vibrio cholerae and Salmonella sp., in fresh fish, during storage phase, at ambient and ice temperatures. Method used in this research is experimental laboratories method, that is, 10%, 20% and 30% blended sea grapes applied on fresh fishes, Selar crumenopthalmus during storage of 1, 2 and 3 days at ambient and ice temperatures. All the applied of blended of Caulerpa lentillifera, shows the ability to obstruct the activity of bactery group coliform and Escherichia coli on fresh fish Selar crumenopthalmus up to 2x 24 hours, at ambient temperature, and 3x24 hours at ice temperature. During storage period, the occurance and grows of Salmonella sp. and Vibrio cholerae bacteries is undetected. Fresh sea grapes concentration of 10% is sufficient to be applied on fresh fish to obstruct the activity of pathogen bacteries Escherichia coli during storage time of 2 x 24 hours at room temperature, and 3 x 24 hours at ice temperature, and to block the occurance of Vibrio cholerae and Salmonella sp. during storage period.